Pengaruh Suhu dan Lama Pengeringan terhadap Kuantitas dan Kualitas Pati Kentang Varietas Granola - Martunis Martunis (Jurnal Teknologi dan Industri Pertanian Indonesia, 2012)
The study aimed to investigate the effects of drying temperature and time to potato starch variety of Granola. Recently, the starch is often used as a raw material for food, pharmaceutical and non-food industries such as textiles, packaging, detergent, etc. Because of unpreserved nature of fresh potato and its quality still reduced during storage, the research was conducted to process potato into semi-finished product in form of starch that expected will enhance the stability during storage, and shipping. The research design used was completely randomized design (CRD) factorial consist of 2 factors. The first factor was the drying temperature (T) consists of 3 levels i.e T1 = 40oC, T2=50oC, and T3 = 60oC. The second factor was drying time (L) consists of 3 levels i.e L1 = 5 hr, L2=6 hr, and L3 = 7 hr. Combination of the treatments was 3 x 3 = 9 with 3 replications, in order to obtain 27 units of the experiment. The analysis of potato starch was made to measure yield, moisture, starch and ash contents, as well as starch brighness. The results showed that drying temperature (T) was highly significant effected to starch yield, moisture, ash content, and starch brighness. While, drying time (L) has significantly effected on moisture and starch brighness. The interaction between temperature and time were not significantly effected to yield, moisture, starch, ash contents, as well as starch brighness. Based on the results, the best quality of potato starch was obtained from the treatment of drying temperature (T1= 40oC) and drying time (L1=5 hr) with the following characteristics: yield (3.61%), moisture content (16.40%), starch content (82.09%), ash content (0.57%), and starch brighness about 54.61%.